2022
DOI: 10.1111/avj.13170
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two techniques to identify the sex of the eastern blue‐tongue skink (Tiliqua scincoides scincoides)

Abstract: Introduction The eastern blue-tongued skink (Tiliqua scincoides scincoides), native to eastern Australia, is commonly kept as both a pet and for breeding. As a sexually monomorphic species, it is important to develop reliable techniques for sex identification, both for breeding and health purposes. Numerous techniques have been developed for the identification of sex in other reptile species but, other than possibly morphometric analysis, none have proven to be reliable in this species. Two techniques showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In conclusion, in addition to morphometry, 11,12,14 a variety of methods have been reported for sexing in Tiliqua scincoides [8][9][10][11]13 but none are entirely adequate in the rehabilitation setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In conclusion, in addition to morphometry, 11,12,14 a variety of methods have been reported for sexing in Tiliqua scincoides [8][9][10][11]13 but none are entirely adequate in the rehabilitation setting.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these procedures is yet to be determined from large studies though McKenzie et al recently reported 100% accuracy using contrast radiography in 20 captivebred Blue Tongues. 9,10,12 Cytogenetic analysis is also accurate but is a very specialized technique. 13 We have, thus, presented a practical and relatively accurate, morphometry-based procedure for sexing Eastern Blue Tongued Skinks that is applicable to the rehabilitation setting as it can be used to eliminate the need to radiograph (or use another more definitive means of sexing) a substantial proportion of rescued Blue Tongues who are most probably male.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations